Assessing Learning Outcomes and Cost Effectiveness of an Online Sleep Curriculum for Medical Students - Bandla, Hari (American Academy of Sleep Medicine, 2012)
OBJECTIVE: Sleep disorders are highly prevalent across all age groups but often remain undiagnosed and untreated, resulting in significant health consequences. To overcome an inadequacy of available curricula and learner and instructor time constraints, this study sought to determine if an online sleep medicine curriculum would achieve equivalent learner outcomes when compared with traditional, classroom-based, face-to-face instruction at equivalent costs. METHOD: Medical students rotating on a required clinical clerkship received instruction in 4 core clinical sleep-medicine competency domains in 1 of 2 delivery formats: a single 2.5-hour face-to-face workshop or 4 asynchronous e-learning modules. Immediate learning outcomes were assessed in a subsequent clerkship using a multiple-choice examination and standardized patient station, with long-term outcomes assessed through analysis of students' patient write-ups for inclusion of sleep complaints and diagnoses before and after the intervention. Instructional costs by delivery format were tracked. Descriptive and inferential statistical analyses compared learning outcomes and costs by instructional delivery method (face-to-face versus e-learning). RESULTS: Face-to-face learners, compared with online learners, were more satisfied with instruction. Learning outcomes (i.e., multiple-choice examination, standardized patient encounter, patient write-up), as measured by short-term and long-term assessments, were roughly equivalent. Design, delivery, and learner-assessment costs by format were equivalent at the end of 1 year, due to higher ongoing teaching costs associated with face-to-face learning offsetting online development and delivery costs. CONCLUSIONS: Because short-term and long-term learner performance outcomes were roughly equivalent, based on delivery method, the cost effectiveness of online learning is an economically and educationally viable instruction platform for clinical clerkships. CITATION: Bandla H; Franco RA; Simpson D; Brennan K; McKanry J; Bragg D. Assessing learning outcomes and cost effectiveness of an online sleep curriculum for medical students. J Clin Sleep Med 2012;8(4):439-443.